Incidence of skin cancers in 3867 patients treated with narrow-band ultraviolet B phototherapy. - Hearn, Ross M Ross; Kerr, Alastair C.; Abd Rahim, Kartini Farah; Ferguson, James; Dawe, Robert Stewart (Wiley-Blackwell, 2008)
Background: Narrow-band ultraviolet B (NB-UVB) phototherapy is a widely used treatment. Psoralen-UVA photochemotherapy (PUVA) increases skin cancer risk and some animal studies have raised the possibility of an increased risk with NB-UVB. The risk of skin cancer in humans following treatment with NB-UVB is unknown.